Інформаційне забезпечення функціонування політичних інститутів: формування теоретико-методологічного каркасу - Цікул, Ірина (Чернівецький національний університет імені Юрія Федьковича, 2021)
The article is devoted to the study of the features of the formation of the theoretical and methodo- logical framework of information support for the functioning of political institutions. The growing im- portance of information in society and the new role of communicative processes that change the politi- cal landscape, naturally aroused interest in the phenomenon of political communication, which in one form or another has always been an integral attribute of the political system. The influence of political communication in the context of a global information society against the background of a qualitative change in the forms and methods of its implementation is not only growing, but also becoming domi- nant. Political communication is associated with the purposeful transmission and selective perception of politically significant information, without which the dynamics of the political process is impossi- ble. Despite the fact that the development of the information society is due to the emergence of inno- vative information technologies, the dissemination of information in it directly depends on the devel- opment of new communication channels and the purposeful building of information flows. The most significant part of communication channels is used in the interests of information support of political activity, as the main element of political communication. As a result of the analysis carried out, information support for the functioning of political institu- tions was determined as one of the directions of political communication and an element of infor- mation policy at the same time. According to the author, it is characterized by a dual nature, since it is both a function of the political system and a component of the political process. Information support in the political sphere provides for the use of all available communication channels in the interests of implementing a political strategy and solving basic problems. In addition, information support forms a kind of “information cushion” necessary to prepare the public for a favorable perception of the politi- cal institution. At the same time, despite the existing theoretical developments, the essence of infor- mation support for the functioning of political institutions remains a poorly studied problem of politi- cal science. The clarity of the scientific understanding of the category “information support for the functioning of a political institution” is also complicated by the vagueness of the interpretation of the term “support”, which determines the content of information activities of subjects.
Information Support for the Functioning of Political Institutions: Formation of Theoretical and Methodological Framework
Keywords: communication, political communication, information, political discourse, information support